2019
DOI: 10.1111/cns.13088
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged febrile seizures induce inheritable memory deficits in rats through DNA methylation

Abstract: Summary Aims Febrile seizures (FSs) are the most common types of seizures in young children. However, little is known whether the memory deficits induced by early‐life FSs could transmit across generations or not. Methods The memory functions of different generations of FS rats were behaviorally evaluated by morris water maze, inhibitory avoidance task, and contextual fear conditioning task. Meanwhile, molecular biology and pharmacological methods were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The diagram confirmed that the DNMT1 gene is a target of miR148a-3p and that there is a close relationship between DNMT1 and the occurrence and development of epilepsy 38 . In addition, epigenetic regulation plays vital roles in nervous system diseases 39 . Among the predicted target genes were many genes strictly related to neuroimmune function, such as SYNJ1, Noggin (NOG), Neuronplastin (NPTN), Nuclear receptor coactivator 1 (NCOA1), and SOS Ras/Rho guanine nucleotide exchange factor 2 (SOS2).…”
Section: Discussionmentioning
confidence: 99%
“…The diagram confirmed that the DNMT1 gene is a target of miR148a-3p and that there is a close relationship between DNMT1 and the occurrence and development of epilepsy 38 . In addition, epigenetic regulation plays vital roles in nervous system diseases 39 . Among the predicted target genes were many genes strictly related to neuroimmune function, such as SYNJ1, Noggin (NOG), Neuronplastin (NPTN), Nuclear receptor coactivator 1 (NCOA1), and SOS Ras/Rho guanine nucleotide exchange factor 2 (SOS2).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of increased susceptibility to chemoconvulsants suggests that hippocampal networks were enduringly altered by the eFSE in a “pro‐epileptogenic” manner. Whereas the current work has not examined memory deficits in eFSE mice, cognitive problems have been robustly identified in eFSE rats, including those who did not develop frank epilepsy 19,55 . Hence, eFSE mice should provide a useful instrument to study hippocampal changes that compromise cognitive functions, a problem now emerging in eFSE‐experiencing children 9 …”
Section: Discussionmentioning
confidence: 90%
“…Whereas the current work has not examined memory deficits in eFSE mice, cognitive problems have been robustly identified in eFSE rats, including those who did not develop frank epilepsy. 19,55 Hence, eFSE mice should provide a useful instrument to study hippocampal changes that compromise cognitive functions, a problem now emerging in eFSE-experiencing children. 9 Interictal spike series and recurrent spontaneous seizures developed in 4 of 24 chronically recorded eFSE-experiencing mice, and no interictal spike series or seizures were identified in euthermic control mice or in mice that had hyperthermia of the same degree and duration but in which eFSE was prevented using diazepam.…”
Section: Context Strengths and Limitations Of The Current Workmentioning
confidence: 99%
“…Then they were moved back to the hyperthermia chamber to elicit the 2nd seizure. For inducing prolonged FS (Dai et al, 2019; Wu et al, 2017), the pups were moved to a cool surface for 2 min once seizure was evoked. Then they were moved back to the hyperthermia chamber.…”
Section: Methodsmentioning
confidence: 99%